PENGARUH BUDAYA MAKAN SIRIH TARHADAP STATUS KESEHATAN PERIODONTAL PADA MASYARAKAT SUKU KARO DI DESA TIGA JUHAR KABUPATEN DELI SERDANG TAHUN 2017 - Lumbantoruan, Mestika (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2019)
Oral health disorder will be impacted on performance of a person. Risk factors for oral diseases include behavior of the society asculture or habitualchewing betel or areca. The aim of researchis to figure out the influence of chewing betel towardshealth status karonesepeopleof Tiga Juhar Deli Serdang in 2016.This research used cross sectional study approach. The research was conducted from February until August 2016 of Tiga Juhar Deli Serdang. The population of research is karonese people who have a habitual chewing betel in Tiga Juhar. The sampleof research was 88 peopleas simple random sampling method. The data collection was done by using primary and secondary data.The analysis of data used univariate, bivariate and multivariate analysis. The results showed that there was no tradition of chewing betel influence to periodontal health status (p = 0.424).There was no value of chewing betel influence to periodontal health status (p= 0.138). There is elemental betel composition influence to periodontal health status (p = 0.022). There is frequency of chewing betel influence to periodontal health status (p = 0.001).There is duration of chewing betel influence to periodontal health status (p = 0.000). The dominant variable is duration of chewing betel influence to periodontal health status (p = 0.032; OR = 2.9), means chewing betel more 5 years is risky 2.9 times periodontal health status than chewing betel less 5 years. Therefore, Tiga Juhar Department of Health must increase the oral health and hygiene status level for karonese people who chewing betel inTiga Juhar.